Effects of cover plate wettability on pool boiling heat transfer in a narrow gap - Rukhsar, Aqsa; Fadda, Dani; Wang, Xiaomeng; Lee, Jungho; You, Seung M. (International Journal of Heat and Mass Transfer, 2024)
An experimental study is conducted to evaluate the effects of cover plate wettability (hydrophobic to hydrophilic) on boiling heat transfer in a narrow horizontal gap (0.64mm to 5mm thick). When the gap thickness is greater than 1mm, the cover plate wettability plays a significant role. A hydrophobic cover plate causes vapor bubbles to move from the heating surface and get attached to the cover plate, maintaining liquid water on the heating surface. When the vapor layer does not reach the heating surface, the nucleate boiling heat transfer coefficient is hardly affected by the gap. However, the critical heat flux (CHF) is reduced relative to the unconfined case as vapor fills the narrow gap. Contrarily, when a hydrophilic cover plate is used with a gap thickness greater than 1mm, a vapor slug forms and hovers over the heating surface with transient lateral movement. Thin liquid film evaporation occurs under the slug, causing an enhanced heat transfer coefficient at low heat flux (q'' < 250kW/m2). As the heat flux increases, the vapor slug movement causes fluctuations in the heater temperature due to partial dryout at the heating surface. Consequently, a rapid decrease in the heat transfer and a reduced CHF are observed relative to the unconfined case. When the gap thickness is reduced to below 1mm, a film boiling-like behavior is observed regardless of the cover plate wettability. However, there is an increase in the heat transfer coefficient at low heat flux (q'' < 250kW/m2).
Keywords: Boiling heat transfer; Cover plate; Cover plate wettability; Gap thickness; Heating surfaces; Hydrophilics; Hydrophobics; Narrow gap; Plate wettability; Vapor slugs; Boiling heat transfer; Cover plate wettability; Hydrophilic; Hydrophobic; Narrow gap